2020
DOI: 10.1017/s1047951120001419
|View full text |Cite
|
Sign up to set email alerts
|

Relation of visceral fat and haemodynamics in adults with Fontan circulation

Abstract: AbstractBeing overweight is associated with reduced functional capacity in Fontan patients. Increased adiposity leads to accumulation of epicardial and intra-abdominal visceral fat, which produce proinflammatory cytokines and may affect endothelial function. This retrospective study to evaluate the association between visceral fat and Fontan haemodynamics included 23 Fontan patients >18 years old with MRI and catheterization data available. Epicardial fat volume indexed to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition, the importance of maintaining a healthy body weight to preserve low pulmonary vascular resistance is increasingly recognized ( 32 ). Importantly, higher BMI often co-exists with increased visceral adiposity (epicardial and intra-abdominal fat), which may be particularly pathological—visceral adiposity is positively associated with pulmonary vascular resistance and inversely associated with ejection fraction and cardiac index in the Fontan circulation ( 35 , 36 ). Of course, BMI may not be a robust measure of adiposity in the setting of complex congenital heart disease, where myopenia is common ( 33 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the importance of maintaining a healthy body weight to preserve low pulmonary vascular resistance is increasingly recognized ( 32 ). Importantly, higher BMI often co-exists with increased visceral adiposity (epicardial and intra-abdominal fat), which may be particularly pathological—visceral adiposity is positively associated with pulmonary vascular resistance and inversely associated with ejection fraction and cardiac index in the Fontan circulation ( 35 , 36 ). Of course, BMI may not be a robust measure of adiposity in the setting of complex congenital heart disease, where myopenia is common ( 33 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that EAT was associated with right ventricular end-diastolic pressure (RVEDP) but not with left-sided filling pressures (pulmonary capillary wedge pressure and LV end-diastolic pressure) [ 68 ]. Another study found a modest correlation between EAT volume and pulmonary vascular resistance in Fontan patients [ 69 ].…”
Section: Section 1: Physiological and Anatomical Features Of Eatmentioning
confidence: 99%